The lion women of tehran ebook - Kamali, Marjan (2024)
NATIONAL BESTSELLER An " evocative read and a powerful portrait of friendship, feminism, and political activism" ( People ) set against three transformative decades in Tehran, Iran—from nationally bestselling author Marjan Kamali. In 1950s Tehran, seven-year-old Ellie lives in grand comfort until the untimely death of her father, forcing Ellie and her mother to move to a tiny home downtown. Lonely and bearing the brunt of her mother's endless grievances, Ellie dreams for a friend to alleviate her isolation. Luckily, on the first day of school, she meets Homa, a kind girl with a brave and irrepressible spirit. Together, the two girls play games, learn to cook in the stone kitchen of Homa's warm home, wander through the colorful stalls of the Grand Bazaar, and share their ambitions of becoming "lion women." But their happiness is disrupted when Ellie and her mother are afforded the opportunity to return to their previous bourgeois life. Now a popular student at the best girls' high school in Iran, Ellie's memories of Homa begin to fade. Years later, however, her sudden reappearance in Ellie's privileged world alters the course of both of their lives. Together, the two young women come of age and pursue their own goals for meaningful futures. But as the political turmoil in Iran builds to a breaking point, one earth-shattering betrayal will have enormous consequences. "Reminiscent of The Kite Runner and My Brilliant Friend , The Lion Women of Tehran is a mesmerizing tale" ( BookPage ) of love and courage, and a sweeping exploration of how profoundly we are shaped by those we meet when we are young.